Ekologi Adab-Cinta di Madrasah Ibtidaiyah: Telaah Filosofis Pendidikan al-Ghazali atas Kurikulum Berbasis Cinta - Nurlailyanna Bisri (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2026)
The Love-Based Curriculum (Kurikulum Berbasis Cinta, KBC) is a recent madrasah education policy that positions love as a foundational principle for character formation, social harmony, and the strengthening of humanistic values. However, KBC may be understood reductively if it is treated merely as a character education program or an administrative curriculum document. This article aims to examine KBC as an ecology of Islamic education in Madrasah Ibtidaiyah through al-Ghazali’s philosophy of education. Employing an integrative literature review with a philosophical inquiry and document analysis approach, this study analyses the official Guideline for the Love-Based Curriculum in Madrasah and al-Ghazali’s works related to mahabbah, knowledge, adab, tazkiyat al-nafs, and action. The findings show that KBC has an ecological structure because it connects spiritual values, knowledge, the self, others, the environment, national identity, madrasah actors, pedagogical practices, leadership, care, evaluation, and socio-emotional outcomes. From al-Ghazali’s perspective, love in KBC is not merely an affective value but a spiritual orientation that generates knowledge, cultivates adab, purifies the soul, and is embodied in ethical action. This article proposes a model of the ecology of adab-love in Madrasah Ibtidaiyah, consisting of six dimensions: theocentric, epistemic, personal, social, ecological, and national. The model contributes to strengthening the philosophical foundation of KBC and to developing a more systemic, relational, and sustainable framework for Islamic primary education.